2023
DOI: 10.3389/fmars.2023.1232923
|View full text |Cite
|
Sign up to set email alerts
|

Plankton community structure in response to hydrothermal iron inputs along the Tonga-Kermadec arc

Zoé Mériguet,
Marion Vilain,
Alberto Baudena
et al.

Abstract: The Western Tropical South Pacific (WTSP) basin has been identified as a hotspot of atmospheric dinitrogen fixation due to the high dissolved iron ([DFe]) concentrations (up to 66 nM) in the photic layer linked with the release of shallow hydrothermal fluids along the Tonga-Kermadec arc. Yet, the effect of such hydrothermal fluids in structuring the plankton community remains poorly studied. During the TONGA cruise (November-December 2019), we collected micro- (20-200 μm) and meso-plankton (>200 μm) sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…Here we show that the POC fluxes were primarily driven by zooplankton derived particles (fecal pellets and aggregates, and zooplankton carcasses), with fecal aggregates dominating at 1000 m, while cylindrical fecal pellets and zooplankton carcasses dominated at 170 m (Table 3; Figure 5). The dominance of zooplankton derived particles is in line with the plankton community composition present in surface waters during the same expedition (Meŕiguet et al, 2023). This latter study reports that grazers, dominated by gelatinous carnivores, chaetognatha, copepoda, and other larger species, account for 34% (average abundance of 329 ind.…”
Section: Composition Of the Sinking Fluxes In The Wtspsupporting
confidence: 76%
See 2 more Smart Citations
“…Here we show that the POC fluxes were primarily driven by zooplankton derived particles (fecal pellets and aggregates, and zooplankton carcasses), with fecal aggregates dominating at 1000 m, while cylindrical fecal pellets and zooplankton carcasses dominated at 170 m (Table 3; Figure 5). The dominance of zooplankton derived particles is in line with the plankton community composition present in surface waters during the same expedition (Meŕiguet et al, 2023). This latter study reports that grazers, dominated by gelatinous carnivores, chaetognatha, copepoda, and other larger species, account for 34% (average abundance of 329 ind.…”
Section: Composition Of the Sinking Fluxes In The Wtspsupporting
confidence: 76%
“…The high POC fluxes derived from zooplankton particles suggest that the Fe-rich hydrothermal inputs from the Tonga arc have stimulated N 2 fixation (Bonnet et al, 2023b), that in turn stimulated primary and secondary productions in this LNLC ecosystem. Meŕiguet et al (2023) showed that diazotrophs dominated the microplankton (20-200 μm) community in the area of trap deployment (69% of the total community abundance of 5.10 5 ind.m -3 ) and that >80% of diazotrophs were Trichodesmium spp. In this ecosystem, diazotrophy supports >80% of export production (Bonnet et al, 2023b).…”
Section: Composition Of the Sinking Fluxes In The Wtspmentioning
confidence: 99%
See 1 more Smart Citation